Factors involved in underground economy increase and analysis of concepts included: Una aproximación a los conceptos incluidos como economía sumergida, así como a los factores más relevantes que la causan - Goenechea Domínguez, María (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Although tax collection is and should be the main source of financing for the State in its function of guaranteeing a minimum of social welfare to citizens, there are circumstances that motivate the taxpayer to evade their tax obligations. This situation causes serious consequences for the economy as well. as important inefficiencies in the allocation of resources, hence the importance of analyzing the factors that cause it in order to try, if not avoid it, reduce it as much as possible.